Implementasi Kebijakan Nilai Pasar Dalam Pemungutan Pajak Mineral Bukan Logam dan Batuan di Kabupaten Karangasem - Kadek Trisna Budhi Suryawan; Ida Ayu Sri Widnyani (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2022)
The establishment of a market value policy is expected to increase the PAD of Karangasem Regency. However, in its application, the Karangasem Regency BPKAD still finds differences in the selling value of non-metallic minerals and rocks among entrepreneurs. This study focuses on the implementation of market value policies in collecting taxes on non-metallic minerals and rocks in Karangasem Regency, obstacles and efforts to overcome obstacles. The study used descriptive qualitative methods and data collection techniques using interview instruments, observation, documentation studies and online searches. The results of the study found that the implementation of the market value policy in collecting taxes on non-metallic minerals and rocks in Karangasem Regency has not run optimally due to several obstacles.